Analisis Efisiensi Relatif di Unit Pelaksana Teknis Badan Pengawas Obat dan Makanan Tahun 2019 - Widyastuti, Pantri; Nurwahyuni, Atik (UI Scholars Hub, 2021)
The challenge of drug and food supervision requires the BPOM Technical Implementation Unit (UPT) to work optimally in the midst of limited resources. The analysis of the relative efficiency of the BPOM Technical Implementation Unit in 2019 was carried out with the aim of improving BPOM's planning, budgeting, and strategic policies in an effort to improve performance at each UPT. Calculation of relative efficiency using the DEA (Data Envelopment Analysis) method. This study uses a mixed method with a cross sectional research design. The research sample was 31 UPT BPOM that met the requirements as DMU (Decision Making Unit), 10 informants in the deepening of the process to determine the factors that affect the efficiency of UPT with DEA. There are 3 inputs and 4 outputs analyzed by DEA. The results of the analysis there are 15 efficient UPT and 16 inefficient UPT. The results of the deepening of the process revealed that the efficient and inefficient UPT had implemented the internal efficiency strategy well. DEA is a relative efficiency analysis with the concept of maximizing the ratio of output and input. The use of the VRS (Variable Return to Scale) model that considers the process, is expected to eliminate the shortcomings contained in the calculation with DEA. DEA calculation is done mechanically, so it is necessary to deepen the process to explore efficiency factors that are not obtained from DEA calculations, especially for organizations that involve large external factors in the process.